2021
DOI: 10.3389/fpubh.2021.666553
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Basic Life Support by Lifeboat Crewmembers While Wearing a Survival Suit and Life Vest: A Randomized Controlled Trial

Abstract: Introduction: Crewmembers of the “Royal Netherlands Sea Rescue Institution” (KNRM) lifeboats must wear heavy survival suits with integrated lifejackets. This and the challenging environment onboard (boat movements, limited space) might influence Basic Life Support (BLS) performance. The primary objective of this study was to assess the impact of the protective gear on single-rescuer BLS-quality.Material and Methods: Sixty-five active KNRM crewmembers who had recently undergone a BLS-refresher course were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…12,16 • The good practice statement on resuscitation in boats was informed by observational and simulation studies showing that it is feasible for rescuers trained in this technique to initiate resuscitation on moving boats. [17][18][19][20][21][22] This recommendation applies to rescue boats and is not meant for the lay public. • Organizations developing guidelines from these recommendations should consider local conditions, including the type and size of the rescue vessel, the number of available rescuers, the availability of equipment and training, and the characteristics of the water and land.…”
Section: Ventilation Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…12,16 • The good practice statement on resuscitation in boats was informed by observational and simulation studies showing that it is feasible for rescuers trained in this technique to initiate resuscitation on moving boats. [17][18][19][20][21][22] This recommendation applies to rescue boats and is not meant for the lay public. • Organizations developing guidelines from these recommendations should consider local conditions, including the type and size of the rescue vessel, the number of available rescuers, the availability of equipment and training, and the characteristics of the water and land.…”
Section: Ventilation Equipmentmentioning
confidence: 99%
“…The good practice statement on resuscitation in boats was informed by observational and simulation studies showing that it is feasible for rescuers trained in this technique to initiate resuscitation on moving boats. 17–22 This recommendation applies to rescue boats and is not meant for the lay public.…”
Section: Basic Life Supportmentioning
confidence: 99%
“…Immediate ventilation, even before the victim is on land, is feasible while the person is still in the water 22 , 41 , 42 , 43 , 44 whilst full CPR, including defibrillation, is possible on a boat. 45 , 46 , 47 , 48 , 49 , 50 This review identified a single study supporting immediate in-water ventilation performed by trained lifeguards over delayed resuscitation upon arrival on land. 22 If attempted, evidence from manikin studies highlight the importance of avoiding unintentional submersion of the patient 42 , 43 , 51 , and the risks of fatigue leading to a failed rescue.…”
Section: Discussionmentioning
confidence: 99%